SCIENTIFIC APPROACH TO THEMATIC LEARNING IN DEVELOPING CRITICAL THINKING SKILLS AT MADRASAH IBTIDAIYAH DARUL ULUM JEMBER - Riska, Dwifitria (IJIT: Indonesian Journal of Islamic Teaching, 2022)
This research is motivated by the lack of critical thinking skills possessed by students, the application of dominant learning is rigid so that it can have a negative impact on students, difficulties in understanding learning problems and can cause a crisis in high-level thinking. Considering that Critical Thinking Skills are needed in the 21st century, thematic learning through a scientific approach can be used as a reference to be able to grow Critical Thinking Skills where the scientific approach is an inseparable part of the 2013 Curriculum. The aims of this research are: (1) To describe observing activities in thematic learning in growing Critical Thinking Skillat MI Darul Ulum Sukorambi Jember (2) Describe questioning activities in thematic learning in growing Critical Thinking Skill at MI Darul Ulum Sukorambi Jember (3) Describe reasoning activities in thematic learning in growing Critical Thinking Skill at MI Darul Ulum Sukorambi Jember (4)Describe trying activities on thematic learning in growing Critical Thinking Skill at MI Darul Ulum Sukorambi Jember (5) Describe communicating activities on thematic learning in growing Critical Thinking Skill at MI Darul Ulum Sukorambi Jember. Methods used is qualitative approach with the type of case study. Data collection techniques were obtained from observation, interviews and documentation. The research location is at Madrasah Ibtidaiyah Darul Ulum Jember, the determination techniqueresearch subjects are determined by purposive sampling technique.Analysis of the data used is using interactive data analysis Milles, Huberman, and Saldana. The validity of the data used in this study issource triangulation and technical triangulation, as well as member check The results of the study are: (1) observing activities include:reading, listening, listening and seeing by using critical thinking worksheets in developingCritical Thinking Skill student (2) Scientific questioning activities include collect questions about information that is not understood from what is observed or questions to obtain additional information about what is observed in scientific activities asking questions in growing Critical Thinking Skill student teacher distributes critical thinking worksheetsin accordance with scientific activities asking questions (3) scientific reasoning activities include processing the information that has been collected based on the results of observations on scientific reasoning activities in growingCritical Thinking Skillstudentteacher distributes critical thinking worksheetsin accordance with scientific reasoning activities (4) scientific activities try to include conducting experiments, reading sources other than textbooks, interviewing resource persons in scientific activities trying to grow Critical Thinking Skill student teacher distributes critical thinking worksheetsin accordance with scientific activities try (5) scientific activities communicate include m . activities convey the results of observations, conclusions based on the results of the analysis orally, in writing or other media in front of the class, in communicating scientific activities in growing Critical Thinking Skill student teacher distributes critical thinking worksheetsin accordance with the scientific activity of communicating.